Atrial Fibrillation Is Associated With Higher Overall Mortality in Patients With Implantable Cardioverter‐Defibrillator: A Systematic Review and Meta‐Analysis. Issue 22 (20th November 2018) - Mustafa, Usman; Dherange, Parinita; Reddy, Rohit; DeVillier, Joseph; Chong, Jessica; Ihsan, Alarozia; Jones, Ryan; Duddyala, Narendra; Reddy, Pratap; Dominic, Paari
Abstract : Background: Implantable cardioverter‐defibrillator (ICD) improves survival when used for primary or secondary prevention of sudden cardiac death. Whether the benefits of ICD in patients with atrial fibrillation (AF) are similar to those with normal sinus rhythm (NSR) is not well established. The aim of this study is to investigate whether ICD patients with AF are at higher risk of mortality and appropriate shock therapy compared with patients with NSR. Methods and Results: Literature was searched and 25 observational studies with 63 283 patients were included in this meta‐analysis. We compared the outcomes of (1) all‐cause mortality and appropriate shock therapy among AF and NSR patients who received ICD for either primary or secondary prevention and (2) all‐cause mortality among AF patients with ICD versus guideline directed medical therapy. All‐cause mortality (odds ratio, 2.11; 95% confidence interval, 1.73–2.56; P <0.001) and incidence of appropriate shock therapy (odds ratio, 1.77; 95% confidence interval, 1.47–2.13; P <0.001) were significantly higher in ICD patients with AF as compared to NSR. There was no statistically significant mortality benefit from ICD compared with medical therapy in AF patients (odds ratio, 0.69; 95% confidence interval, 0.42–1.11; P =0.12) based on a separate meta‐analysis of 3 studies with 387 patients. Conclusions: Overall mortality and appropriate shock therapy are higher in ICD patients with AF as compared with NSR. The impact of ICD on all‐cause mortality in AF patients when compared to goal‐directed medical therapy is unclear, and randomized controlled trials are needed comparing AF patients with ICD and those who have indications for ICD, but are only on medical therapy.